The Buas Buas Leaf Utilization of Buas Buas Leaf (Premna pubescens Blume) Ethanol Extract as Liquid Soap With Anti-Bacteria Activity - Rafita, Rafita Yuniarti; Munandar Nasution, Haris; Rani, Zulmai; Fahmi, Fahmi (International Journal of Science, Technology & Management, 2022)
The buas buas (Premna pubescens Blume) plant is from the Lamiaceae family. The use of ethanol extract of buas buas leaf (Premna pubescens Blume) as soap is because soap is one of the health products needed by many people to maintain a healthy body. It is used as an antibacterial because buas buas leaves contain secondary metabolites that can be used as antibacterial.The Buas buas leaf Simplicia (Premna pubescens Blume) was extracted using 96% ethanol by maceration and concentrated with a rotary evaporator to evaporate the solvent. The concentrated extract obtained was tested by phytochemical screening, formulated into liquid soap with concentrations of 5%, 10%, 15% and tested for pH, foam height, viscosity, specific gravity and irritation test, and antibacterial activity against staphylococcus aureus bacteria. The results of the phytochemical screening test of the ethanol extract of buas buas leaf (Premna pubescens Blume) contained secondary metabolites in the form of alkaloids, flavonoids, saponins, tannins and steroids/triterpenoids. Liquid soap made with concentrations of 5%, 10%, and 15% has a pH of 10-10.3; foam height 50-90 mm; viscosity 1210-1290 cP; specific gravity 1-1.08 and did not cause irritation to volunteers; and have inhibitory power of 14.2 mm, 15.0 mm, 16.0 mm, and 20.0 mm against Staphylococcus aureus bacteria, respectively.